2015
DOI: 10.1159/000441516
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Views on Longer Storage of Neonatal Dried Blood Spots for Specific Secondary Uses

Abstract: Background: Neonatal dried blood spots (DBS) present a wealth of data. Currently, many countries discuss DBS storage, management and use. We collected data in the Netherlands on the awareness and views of an unheard stakeholder: mothers (-to-be). Methods: A survey was conducted on an Amsterdam pregnancy fair website in 2011. We included 1,272 women who were pregnant and/or had at least one child ≤5 years old. A descriptive analysis was used to score the awareness of and views on policies regarding the length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…From both the opinion survey and the focus groups, we observed that many parents were not aware of the potential value of rDBS before taking part in the study. A low awareness of the retention of rDBS and its potential value in population health have been similarly reported in previous studies [ 28 , 29 ]. A discussion on the topic has been shown to help parents feel positive about retention and secondary use of rDBS [ 14 ].…”
Section: Discussionsupporting
confidence: 65%
“…From both the opinion survey and the focus groups, we observed that many parents were not aware of the potential value of rDBS before taking part in the study. A low awareness of the retention of rDBS and its potential value in population health have been similarly reported in previous studies [ 28 , 29 ]. A discussion on the topic has been shown to help parents feel positive about retention and secondary use of rDBS [ 14 ].…”
Section: Discussionsupporting
confidence: 65%
“…According to a study carried out in the Netherlands, Dutch mothers lean towards supporting secondary use of this data. However, more efforts are required in order to involve parents in developing policies that deal with DBSs [57]. Several researchers have used DBS data to gain more insight into different conditions and disorders.…”
Section: B Secondary Use Of Patient Data For Genomic Research and Tomentioning
confidence: 99%
“…These points bear on both the results of this study and their significance. Awareness of DBS research is ubiquitously low (Botkin et al 2014;van Teeffelen et al 2016;Davis et al 2006;Newcomb et al 2013), and criticism and controversy have arisen over real or perceived lack of transparency about routinized storage. National studies find that people want to know that they are biobank participants and prefer to have the option to choose to participate (Botkin et al 2013;Rothwell et al 2012;Tarini et al 2010b;Garrison et al 2015).…”
Section: Content Analysismentioning
confidence: 99%
“…A consistent finding from the global literature on newborn screening, biobanking, and genetic research is the need to strengthen public engagement and education efforts to improve public awareness and understanding, assess opinion and expectations, foster inclusive discussion, and to inform and ensure ethical practices and policies in these contexts (Simon et al 2011;Botkin et al 2013;Rothwell et al 2010;Botkin et al 2014;Davey et al 2005;Etchegary et al 2013;Goldenberg 2009;Bombard et al 2012;Cañada et al 2015;van Teeffelen et al 2016;Davis et al 2006). The literature has called for improved, parent-centered educational materials (Botkin et al 2013); improved timing of education to allow parents to process information in the prenatal period, rather than within 72 h of childbirth (Botkin et al 2013;Rothwell et al 2010;Davey et al 2005;Davis et al 2006); public engagement to help guide policy and diverse community engagement methods to account for diverse contexts and communities (Etchegary et al 2013); informing of participants to legitimize opt-out policies (Goldenberg 2009); and further qualitative research to better understand parent and public attitudes about DBS storage and genetic research (Bombard et al 2012;van Teeffelen et al 2016;Rothwell et al 2012).…”
Section: Introductionmentioning
confidence: 96%